Formation of Competence Paradigm in Teaching of Physics in the School Education of Ukraine: Experience of Theory and Practice - N. Golovko (Oriental Studies, 2018)
The article deals with the problems of theoretical substantiation of competence approach and its implementation in teaching of Physics at general education school in Ukraine. There is showed commonality of methodological prerequisites of transformation of content and methods of teaching of Physics in general education school. The author reveals the main directions and didactic condition of purposeful formation of subject competence in physics as a part of natural-science competence of school leaver.